Learning Burnout: Evaluating the Role of Social Support in Medical Students - Zhang, Jia-Yu; Shu, Tao; Xiang, Ming; Feng, Zhan-Chun (Frontiers in Psychology, 2021)
Background: Burnout is a stress-induced syndrome that is considered closely related to work. Although social support could reduce burnout syndrome, the effect of it on learning burnout in medical students remains unclear. The objectives of the study are to evaluate the association between learning burnout and social support in a cohort of Chinese medical students. Methods: A cross-sectional online survey was distributed to students who participated in online learning in a medical college in Wuhan during the COVID-19 epidemic. We used the Lian version of the Maslach Burnout Inventory (MBI) to assess learning burnout and the Social Support Rating Scale (SSRS) to assess social support. Chi-square test was used to analyze factors associated with burnout and independent t-test and bivariate logistic regression were used to analyze the relatonship between social support and burnout. Results: A total of 684 students completed the survey (response rate of 30.9%), of which 315 (46.12%) met standard criteria for learning burnout. Chi-square analysis revealed that grade, family income, learning time, and the number of interactions with teachers or classmates were significant predictors of learning burnout (p < 0.01). After adjusting for the grade and residence, there was a significant and relevant association between the social support and learning burnout. (adjusted odds ratio, 0.93 for 1-point decrease in total SSRS score; 95% CI, 0.90 – 0.96; p < 0.001). Conclusions: Learning burnout was highly prevalent in medical students of our college. Senior students, low family income, reduced learning time, and low frequnecy communication with teachers or classmates were significant and strong risk factors for learning burnout. The social support especially subjective support and utilization of support played a protective role in reducing the risk of learning burnout.